Stages of codification of All-Union criiminal procedural legislation in the Soviet period - T. F. Yashchuk (Правоприменение)
The subject of the study is the criminal procedural legislation of the Soviet period. The purpose of the article is to highlight and characterize the stages of codification of all-Union criminal procedure legislation. The stages are highlighted taking into account changes within the two-level structure of sectoral legislation, which reflect the evolution of the Soviet state and law. All-Union codified acts were designated by the term Fundamentals. The article proves that in the conditions of a federal state, the optimal structure for criminal procedural legislation included the all-Union Fundamentals and the Republican Code. Attempts to compile a Criminal Procedure Code of the USSR were unsuccessful. The main research methods are the comparative legal method and the formal legal method. They were used to analyze and compare regulations and proposed projects. The chronological method was used to highlight the stages of codification of the all-Union criminal procedural legislation. The institutional method made it possible to consider criminal proceedings as an independent branch related to public law. Based on published and archival sources, the reasons, conditions, stages and results of codification are explored. For the first time, projects of the USSR Code of Criminal Procedure were identified and analyzed.Two stages of codification activity are identified, the border between them being the Constitution of the USSR of 1936. At the first stage, the Fundamentals of Criminal Proceedings of the USSR and Union Republics of 1924 were approved. The foundations were based on the provisions of the Code of Criminal Procedure of the RSFSR of 1922. At the second stage, significant efforts were spent on drawing up the Code of Criminal Procedure of the USSR. The activities of special commissions involved in the preparation of the USSR Code of Criminal Procedure in the 1930-50s are considered. The termination of the development of the USSR Code of Criminal Procedure had political reasons not related to the quality of the projects. Positive results of codification activities are shown. The drafting of the USSR Code of Criminal Procedure contributed to the development of the theory of codification and the doctrine of criminal procedure legislation. Project materials were used in the preparation of the Fundamentals of Criminal Procedure of the USSR and Union Republics of 1958 and the Code of Criminal Procedure of the RSFSR of 1960.A conclusion is made about the high continuity of basic norms and institutions in the codified acts on criminal proceedings of the Soviet period. The study provides an example of the construction and development of the vertical structure of legislation in a federal state.